1H NMR-Based Metabolomics Reveals Refined-Huang-Lian-Jie-Du-Decoction (BBG) as a Potential Ischemic Stroke Treatment Drug With Efficacy and a Favorable Therapeutic Window - Fu, Xiaowei; Wang, Junsong; Liao, Shanting; Lv, Yan; Xu, Dingqiao; Yang, Minghua; Kong, Lingyi (Frontiers in Pharmacology, 2019)
Huang-Lian-Jie-Du-Decoction (HLJDD) is a traditional Chinese medicine used to treat ischemic stroke. However, the complexity of its chemical composition makes it difficult for its quality control. Berberine, baicalin, and geniposide are the three main ingredients in HLJDD. Here, a formula BBG comprising berberine, baicalin, and geniposide, named as Refined-Huang-Lian-Jie-Du-Decoction, was investigated for its efficacy, therapeutic window, and mechanisms of action. BBG was assessed on two major types of ischemic stroke, cerebral ischemia-reperfusion (I/R) injury and continuous ischemia injury, respectively. BBG showed efficacy comparable to HLJDD in the treatment of cerebral I/R injury within 5 hours after the injury initiation, but did poorly in treating continuous ischemia injury. BBG exhibited neuroprotective effects on cerebral I/R injury by regaining the balance in energy metabolism, oxidative stress, amino acid metabolism, inflammation, and nucleic acid metabolism. These results suggested that BBG could be a good alternative to HLJDD with high efficacy and a long therapeutic window, which is of great potential for drug development to treat stroke.